2016
DOI: 10.1007/s10067-016-3309-7
|View full text |Cite
|
Sign up to set email alerts
|

Tendon involvement in patients with gout: an ultrasound study of prevalence

Abstract: The objective of the present study is to evaluate, by ultrasonography (US), the prevalence in the quadriceps, patellar, and Achilles tendon involvement of gout compared to that of patients with osteoarthritis and asymptomatic marathon runners. This is a multicenter, multinational, transverse cross-sectional, and comparative study comprising 80 patients with the diagnosis of gout according to the American College of Rheumatology (ACR) criteria, compared with two control groups: 35 patients with generalized oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 32 publications
3
25
0
Order By: Relevance
“…We observed intratendinous hyperechoic deposits in 35.9% of participants with MSU crystal deposits elsewhere. This is consistent with previous reports of tendon involvement in gout (14,15). As shown in Table 2, a substantial proportion of tendon hyperechoic deposits occurred in subjects without ultrasonographic features of MSU crystal deposition in the first MTP joints.…”
Section: Discussionsupporting
confidence: 93%
“…We observed intratendinous hyperechoic deposits in 35.9% of participants with MSU crystal deposits elsewhere. This is consistent with previous reports of tendon involvement in gout (14,15). As shown in Table 2, a substantial proportion of tendon hyperechoic deposits occurred in subjects without ultrasonographic features of MSU crystal deposition in the first MTP joints.…”
Section: Discussionsupporting
confidence: 93%
“…Using shear wave elastography, we have for the first time, demonstrated that people with gout have significantly lower stiffness in the AT compared with age/sex matched non-gout participants. Tendon pathology in the lower limbs has been shown to be more frequent in those with gout than those with osteoarthritis or healthy controls [36]. The AT is reported to be a commonly involved site in tophaceous gout.…”
Section: Discussionmentioning
confidence: 99%
“…Tendon pathology in the lower limbs has been shown to be more frequent in those with gout than in those with either osteoarthritis or healthy controls. [13,47] A systematic review and meta-analysis revealed that abnormal ultrasound ndings (i.e. tendon thickening, increased vascularity, hypoechogenicity) in the AT were predictive of tendinopathy.…”
Section: Discussionmentioning
confidence: 99%